2022
DOI: 10.3389/fcimb.2022.726322
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Gut Microbiota Composition and Metabolites Associated With Feeding Intolerance in VLBW Infants With a Gestational Age of ≤ 30 Weeks: A Pilot Study

Abstract: ObjectiveTo explore the main variations in gut microbiota compositions, short-chain fatty acids (SCFAs) concentrations and autoinducer-2 (AI-2) levels in very-low-birth-weight (VLBW) infants with feeding intolerance (FI).MethodsTwenty-seven VLBW infants with gestational ages of ≤30 weeks were divided into the FI group (n=14) and feeding tolerance (FT) group (n=13). The gut microbiota composition and SCFAs concentrations and AI-2 levels in feces were detected at 2 and 4 weeks after birth.ResultsThere was no dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…The infants enrolled in our study were those who presented with gastrointestinal symptoms, and those in Group C were mostly diagnosed with FI. FI can lead to a decrease in diversity and changes in beta diversity, and studies have shown a pattern similar to NEC in patients who developed FI ( La Rosa et al, 2014 ; Li et al, 2021 ; Liu et al, 2022 ), which can explain why the diversity showed no differences in our study.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The infants enrolled in our study were those who presented with gastrointestinal symptoms, and those in Group C were mostly diagnosed with FI. FI can lead to a decrease in diversity and changes in beta diversity, and studies have shown a pattern similar to NEC in patients who developed FI ( La Rosa et al, 2014 ; Li et al, 2021 ; Liu et al, 2022 ), which can explain why the diversity showed no differences in our study.…”
Section: Discussionsupporting
confidence: 55%
“…Genomic DNA of the fecal microbiota was extracted with a QIAamp FAST DNA Stool Mini-Kit (Qiagen, Hilden Germany) as previously described ( Liu et al, 2022 ). DNA extracts were tested on a 1% agarose gel, and the concentration and purity were assessed with a spectrophotometer (NanoDrop 2000 UV–vis, Thermo Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of the microbiome on compensatory growth or extrauterine growth restriction (EUGR) was not included because the weight of most of the SGA infants was still below the 10th percentile at the time of discharge. Feeding, weight gain, and catch-up growth are related to microbial community structure [ 10 , 22 , 52 , 53 , 54 , 55 ]. In a rat model, the decrease in the abundance of Lactobacillus was significantly associated with catch-up growth [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathogenesis of NEC is complex and multifactorial, large amounts of evidence have reported that gut microbiota dysbiosis plays an essential role in NEC occurrence and progression ( Claud and Walker, 2001 ; Tarracchini et al., 2021 ). Previous studies revealed that neonates with NEC have significantly different gut microbiomes than non-NEC neonates ( Liu et al., 2022b ): the diversity of bacteria is reduced, and the abundance of Enterobacteriaceae is increased in neonates with NEC, which can activate TLR4 and promote NEC progression ( Shaw et al., 2021 ). Additionally, with the change in the gut microbiota, metabolites show corresponding changes; the affected metabolites are generally considered to act as a bridge between flora and host communication and may also be involved in the pathogenesis of NEC ( Krautkramer et al., 2021 ; Zhou et al., 2022a ).…”
Section: Introductionmentioning
confidence: 99%